2016
DOI: 10.12669/pjms.323.9635
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric measurements may be informative for nursing home-acquired pneumonia

Abstract: Objective:To evaluate the relationship between anthropometric measurements and Nursing Home-Acquired Pneumonia (NHAP) risk.Methods:Consecutive patients of 65 years or elderly who were living in the Balikli Rum Hospital Nursing Homes were included in this prospective study. At the beginning of this study, the patients’ anthropometrics values were measured. The patients were followed for one year, and any incidences of pneumonia attacks were recorded. The relationship between the anthropometric measurements and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
1
5
0
2
Order By: Relevance
“…A study showed that patients who were entered into the Intensive Care Unit (ICU) due to the need for mechanical ventilation had a more positive correlation between respiratory insufficiency and sarcopenia [ 29 ]. Another study found that sarcopenia and pneumonia were closely related, which supports our conclusion [ 30 ]. Moreover, a study from Peru showed a higher incidence rate of community-acquired pneumonia among subjects diagnosed with sarcopenia [ 31 ].…”
Section: Discussionsupporting
confidence: 91%
“…A study showed that patients who were entered into the Intensive Care Unit (ICU) due to the need for mechanical ventilation had a more positive correlation between respiratory insufficiency and sarcopenia [ 29 ]. Another study found that sarcopenia and pneumonia were closely related, which supports our conclusion [ 30 ]. Moreover, a study from Peru showed a higher incidence rate of community-acquired pneumonia among subjects diagnosed with sarcopenia [ 31 ].…”
Section: Discussionsupporting
confidence: 91%
“…Signs and symptoms of pneumonia may include chest pain, cough, fatigue, fever, nausea, vomiting or diarrhea, and shortness of breath. In addition, in a less active lifestyle, the consequence of the patients with pneumonia leads to malnutrition and higher mortality rates [3]. Patients with pneumonia become malnourished (e.g., protein-calorie malnutrition), exhibit declining health and changes in weight loss, and seriously impair respiratory muscle contractility and endurance [4].…”
Section: Introductionmentioning
confidence: 99%
“…Reduced nutrient intake leads to poor nutritional status and aggravates infection in elderly patients ( 25 ). Poor nutritional status damages respiratory function, thus impairing immune function and increasing pneumonia ( 26 , 27 ). Adequate nutrition can enhance respiratory muscle function and immune defense ( 28 , 29 ).…”
Section: Discussionmentioning
confidence: 99%